El examen biomecánico mediante plataformas baropodométricas - Avagnina, Luca (Revista Internacional de Ciencias Podológicas, 2007)
The podobarometrics platforms represent a trustworthy and cuantificable method for the study of the human gait and for the aid to the diagnosis of certain anatomical, functional and biomechanics alterations in the lower limb. However, they do not represent a method, that by itself can be able to establish a pathological clinical diagnosis of the locomotive apparatus and/or the foot. Nevertheless, its use as complement to other techniques of diagnosis and exploration is very useful at the time of carrying out an accurate diagnosis in pathology of the foot. In this article we exposes a clear and simple way to understand the podobarometrícs methodology and its application in the field of the Podyatry.